2016
DOI: 10.1002/eji.201545843
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis‐specific CD4+ T‐cell response is increased, and Treg cells decreased, in anthelmintic‐treated patients with latent TB

Abstract: In many settings, adults with active or latent tuberculosis will also be coinfected with helminths. Our study aimed to investigate how anthelmintic treatment modulates antimycobacterial immunity, in a setting where helminth reinfection should not occur. Additional supporting information may be found in the online version of this article at the publisher's web-site We investigated the potential impact of helminth infection on immune responses to Mycobacterium tuberculosis (Mtb) in patients with latent Mtb infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 50 publications
3
32
2
Order By: Relevance
“…We have previously shown that downmodulation of TLR expression and function was partially reversible by anti-filarial treatment in filarial-LTB coinfection (21). More recently, anthelmintic treatment was shown to significantly improve the Th1 response and downregulate the regulatory T cell response in helminth-LTB coinfection (14). Our study data thus add to the literature on the modulation of immune response following treatment of helminth infection in the setting of coinfections.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We have previously shown that downmodulation of TLR expression and function was partially reversible by anti-filarial treatment in filarial-LTB coinfection (21). More recently, anthelmintic treatment was shown to significantly improve the Th1 response and downregulate the regulatory T cell response in helminth-LTB coinfection (14). Our study data thus add to the literature on the modulation of immune response following treatment of helminth infection in the setting of coinfections.…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, hookworm infections are known to modulate Th1 and Th17 responses in an antigen-specific manner in latent TB (13). Both S. stercoralis and schistosomes are known to enhance regulatory T cell responses, which in turn downmodulate Th1 responses in latent TB (14). Finally, S. stercoralis infection is also known to influence the systemic responses of cytokines, including type 1, type 2, and type 17 cytokines, and other proinflammatory responses in coinfected individuals (10).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Strongyloides and Mtb co-infection has also been shown to be associated with significantly lower systemic levels of type 1 (IFNγ, TNFα and IL-2) and Th17 (IL-17A and IL-17F) cytokines and significantly elevated systemic levels of regulatory (IL-10 and TGFβ) and type 2 (IL-4, IL-5 and IL-13) cytokines ex vivo [75]. In addition, a study of immigrants to the United Kingdom demonstrated that helminth infections (mainly Schistosoma mansoni and S. stercoralis ) were associated with a decreased frequency of CD4 + IFNγ secreting T cells and an increased frequency of CD4 + Tregs in those with LTBI in comparison to helminth-uninfected controls [76]. Interestingly, following anthelmintic treatment, the frequency of Th1 cells increased and that of Tregs decreased, indicating that the modulation of T cell responses was helminth-mediated.…”
Section: Helminth - Tuberculosis Co-infectionmentioning
confidence: 99%